2002
DOI: 10.1242/jcs.00037
|View full text |Cite
|
Sign up to set email alerts
|

PKCα-mediated ERK, JNK and p38 activation regulates the myogenic program in human rhabdomyosarcoma cells

Abstract: We have previously suggested that PKCα has a role in 12-O-Tetradecanoylphorbol-13-acetate (TPA)-mediated growth arrest and myogenic differentiation in human embryonal rhabdomyosarcoma cells (RD). Here, by monitoring the signalling pathways triggered by TPA, we demonstrate that PKCα mediates these effects by inducing transient activation of c-Jun N-terminal protein kinases (JNKs) and sustained activation of both p38 kinase and extracellular signal-regulated kinases (ERKs) (all referred to as MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 56 publications
9
100
3
Order By: Relevance
“…7, A and B, IGFBP-6 transiently increased phosphorylation of p38 MAPK. We and others have shown previously that ERK1/2 is constitutively activated in RD cells, whereas IGF treatment has no further effect (23,27,28). The present study confirmed a high level of constitutive ERK1/2 phosphorylation (Fig.…”
Section: Igfbp-6 Induces Tumor Cell Migration In An Igf-independentsupporting
confidence: 91%
“…7, A and B, IGFBP-6 transiently increased phosphorylation of p38 MAPK. We and others have shown previously that ERK1/2 is constitutively activated in RD cells, whereas IGF treatment has no further effect (23,27,28). The present study confirmed a high level of constitutive ERK1/2 phosphorylation (Fig.…”
Section: Igfbp-6 Induces Tumor Cell Migration In An Igf-independentsupporting
confidence: 91%
“…60,61 Thus, our results suggest that expression and activation of RAGE in cells of the myogenic lineage might cause proliferation arrest, a critical event in the process of myoblast differentiation and in the control of neoplastic transformation. Consistent with this conclusion is the finding that the extent of phosphorylation (activation) of JNK, a mitogenic kinase particularly active in RMS cells and suggested to play an important role in rhabdomyosarcomagenesis, 47,48 is remarkably reduced in TE671/RAGE cells, compared with TE671/wt and TE671/RAGE⌬cyto cells, again in a p38 MAPK-dependent manner ( Figure 3B). In addition, as mentioned above, forced expression of RAGE in TE671 cells results in down-regulation of expression of cyclin D1 ( Figure 5I), which is overexpressed in highly proliferating, metastatic cells, including RMS cells, has an important role in cellular survival and DNA synthesis, and is induced by sustained activation of ERK1/2.…”
Section: Discussionsupporting
confidence: 74%
“…47,48 Administration of the JNK inhibitor SP600125 to TE671/RAGE cells in DM caused a threefold stimulation of MCK induction compared with untreated TE671/RAGE cells ( Figure 4A), suggesting that (excessive) activation of JNK reduced RAGE promyogenic activity and that, conversely, RAGE signaling to MKK6/p38 MAPK was able to overcome JNK antimyogenic activity in TE671/RAGE cells in part. Consistently, TE671/ RAGE⌬cyto and TE671/wt cells exhibited remarkably higher levels of JNK phosphorylation (activation) compared with TE671/RAGE cells in GM and in DM, and inhibition of p38 MAPK with SB203580 in TE671/RAGE cells resulted in levels of JNK phosphorylation comparable with those found in TE671/RAGE⌬cyto and TE671/wt cells ( Figure 4B).…”
Section: Rage Engagement By Hmgb1 In Te671/rage Cells Activates the Pmentioning
confidence: 99%
“…Recently, there have been reports of PKC relaying its intracellular signals through MAPK activation (Ito et al, 2001;Miao et al, 2001;Braz et al, 2002;Chen et al, 2002;Mauro et al, 2002). It would be interesting to know whether the PKCs down-regulated by PMA relay their signals via MAPK in HUVE-DCs.…”
Section: Resultsmentioning
confidence: 99%